Study of sensory characteristics of poultry meat obtained with the use of modern stunning technology - Shalginbayev, D. B. (International Journal of Advanced Science and Technology, 2020)
The article presents studies of color and aromatic characteristics of poultry meat samples obtained using the traditional method of stunning (using electric current) and gas stunning. Three samples of poultry meat (broiler) obtained by different methods of stunning different manufacturers are given: Kazakhstan, electrical stunning-1; Russia, gas stunning-2; Russia, electrical stunning-3. The meat was taken from 2 parts of the carcass: the round and the breast. Modern methods of studying color and aromatic characteristics allow to get adequate information about the processes occurring in poultry meat after slaughter and about the influence of stunning methods on the color characteristics and odor of meat. It is noted that the round meat has an identical color for all the studied samples. For breast meat, there is a slight decrease in the proportion of the red component of the color, the meat becomes grayer, while the color intensity of samples 1 and 3 decreases – for sample 1 by 17 %, for sample 3-by 11 %. The breast meat of the sample 2, despite the change in color intensity relative to the round of the same manufacturer, preserved. The results of studying the gas phase over meat samples did not show significant differences in the quality of meat. Comparison of the impact of stunning methods on the quality of meat proves that both methods are effective and contribute to the production of meat of excellent quality.В статье представлены исследования цветовых и ароматических характеристик образцов мяса птицы, полученных с использованием традиционного метода оглушения (с использованием электрического тока) и оглушения газом. Приведены три образца мяса птицы (бройлера), полученные разными способами ошеломления разных производителей: Казахстан, Ошеломление электрическое-1; Россия, газ потрясающий-2; Россия, электрика потрясающая-3. Мясо было взято из 2 частей туши: раунд и грудка. Современные методы изучения цветовых и ароматических характеристик позволяют получить адекватную информацию о процессах, происходящих в мясе птицы после убоя, и о влиянии ошеломляющих методов на цветовые характеристики и запах мяса. Отмечено, что круглое мясо имеет одинаковый цвет для всех исследованных образцов. Для грудного мяса наблюдается небольшое уменьшение доли красного компонента цвета, мясо становится более серым, а интенсивность окраски образцов 1 и 3 уменьшается - для образца 1 на 17%, для образца 3 - на 11% , Мясо грудки образца 2, несмотря на изменение интенсивности окраски по отношению к туру того же производителя, сохранилось. Результаты изучения газовой фазы на образцах мяса не показали существенных различий в качестве мяса. Сравнение влияния ошеломляющих методов на качество мяса доказывает, что оба метода эффективны и способствуют производству мяса отличного качества.
Keywords: импакт-фактор 2020; научный журнал; скопус; мясо птицы; зарубежное издание; технология мяса; дальнее зарубежье; периодическое издание; безопасность пищевых продуктов; poultry meat; метод оглушения; stunning; aromatic characteristics; процентиль 29; colorimetric characteristics; q 3; зарубежные авторы